Exporting and Labor Demand: Micro-level Evidence from Germany - Andreas Lichter; Andreas Peichl; Sebastian Siegloch (Center for Economic Studies and ifo Institute (CESifo), 2014)
It is widely believed that globalization affects the extent of employment and wage responses to economic shocks. To provide evidence for this, we analyze the effect of firms' exporting behavior on the elasticity of labor demand. Using rich, German administrative linked employer-employee panel data from 1996 to 2008, we explicitly control for self-selection into exporting and endogeneity concerns. In line with our theoretical model, we find that exporting at both the intensive and extensive margins significantly increases the (absolute value of the) unconditional own-wage labor demand elasticity. This is not only true for the average worker, but also for different skill groups. For the median firm, the elasticity is three-quarters higher when comparing exporting to non-exporting firms.
Keywords: F16; F66; J23; 330; trade; export; labor demand; wage elasticity; administrative microdata